MEASURING APPARATUS FOR ORAL CAVITY, OCCLUSION EVALUATION SYSTEM, AND PROGRAM - KUROKOME HARUYORI; KONNO NORIHITO (2016)
PROBLEM TO BE SOLVED: To transmit an occluded state within the oral cavity while keeping battery consumption low.SOLUTION: A mouthpiece 10 is driven by a battery 40. A sensing part 20, which comprises sensors 200-1 to 200-n, detects a subject's occluded state. A transmission timing setting part 31 sets data transmission timing on the basis of the occluded state detected by the sensing part 20. A transmission part 33 transmits the occluded state detected by the sensing part 20, on the basis of the data transmission timing determined by the transmission timing setting part 31. 【課題】バッテリの消費量を抑えつつ口腔内の咬合状態を送信すること。【解決手段】マウスピース１０は、バッテリ４０によって駆動する。センシング部２０は、センサ２００−１〜２００−ｎから構成され、被験者の咬合状態を検出する。送信タイミング設定部３１は、センシング部２０が検出した咬合状態に基づいて、データ送信タイミングを設定する。送信部３３は、送信タイミング設定部３１が定めたデータ送信タイミングに基づいて、センシング部２０が検出した咬合状態を送信する。【選択図】図２